KONSEP MATERI BILANGAN DALAM AL – QUR’AN DAN HADITS - Asrori Septa Sugianto; Nila Alfi Rosyidah, I’anatul Muhtaromah, Anisa Ela, Mohammad Kholil (Jurnal Salome : Multidisipliner Keilmuan, 2023)
Muslims are guided by the Al-Qur'an and Hadith, which not only discuss religion but also several fields of science, including mathematics. Many verses of the Qur'an and hadith deal with mathematical ideas, including numbers. As a result, the concept of numbers in the Qur'an and hadith has become of interest to researchers. The reason for conducting this examination is to investigate the problem of numbers contained in the Al-Qur'an and hadith. The method used is library research method. Document review and data analysis techniques using content analysis techniques were used to collect data. Research findings: 1). the idea of number assignment in the Qur'an, the repetition of the Qur'an related to number activities are incorporated in Q.S Al-Kahf: 25. Q.S. Al-Baqarah Al-'ankabut, Q.S. 261, 14, and Q.S An-Nur: 2. 2). The idea of partial numbers in the surahs of the Qur'an is related to fractional numbers, especially QS. A Nisa' chapter 11, and QS. Verse 20 of Al Muzammil 3). The hadiths about the primacy of night prayer, the virtue of marriage, and the primacy of a special person in his prayer are hadiths related to fractional numbers.